PENGUATAN BUDAYA LITERASI DI PESANTREN - Maskur, Abu (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2019)
Islamic boarding school is the oldest Islamic education institution in Indonesia. The yellow book which is a compulsory curriculum is the root of literacy culture in Islamic boarding schools. The development of technology and information is one of the reasons for the decline in literacy in Indonesian society, including in Islamic boarding schools. Thus, strengthening the literacy culture in Islamic boarding schools needs to be done.